L’environnement financier au Canada : au coeur de l’impasse - Glorieux, Guy (Assurances)

(untitled) (HEC Montréal, 1982)
Speaking to the Conference Board in Montreal on June 22nd 1982, Mr. Guy Glorieux said he was very unhappy with Canada's current situation. We believe that he is right to be pessimistic, unless of course firm political decisions are taken to improve the position. In the past, Canada has managed to survive various difficulties and even crises. To come through the present situation, we have to understand what is happening and be ready, as individuals and collectively, to follow the lead of capable and resolute leaders.